Reducing Sugar Production in Subcritical Water and Enzymatic Hydrolysis Using Plackett-Burman Design and Response Surface Methodology - Maktum Muharja; Irfan Albana; Jayyid Zuhdan; Agra Bachtiar; Arief Widjaja (Jurnal Teknik ITS, 2019)
Subcritical water is one method of hydrolysis that can convert coconut husk to produce reducing sugars. However, this method has the disadvantage of producing derivative products such as furfural and phenolic compounds that act as inhibitors. One effective method is the addition of additives to the subcritical water process. The purpose of this study was to determine the effect of adding additives to subcritical water processes and optimizing the operating conditions on the production of reducing sugars. The analysis of reducing sugar was conducted by the dinitrosalicylic acid (DNS) method. Variables used in this study were time, temperature, pressure, water volume, pH, and several types of additives. Plackett-Burman was used for screening significant factors for the production of reducing sugars. The three most affecting factors were further investigated to find out the optimum point using Response Surface Methodology (RSM). The optimum point for subcritical water pretreatment operating conditions was the addition of sodium dodecyl sulfate (SDS) of 0.24 grams, reaction time for 80 minutes, and pH 11 yielding a reducing sugar yield of 22.7%, energy use of 291.3 kJ/g with desirability of 85%. Furfural content of all liquids after pretreatment can be neglected (<2 ppm) because of the effect of surfactant.